Development of aligned carbon nanotubes for interconnects applications - Lu, Jingyu. (2013)
The demand for faster, cheaper, more compact and multifunctional electronic products has been pushing the dimensions of transistors and interconnects towards the physical limit, various problems arise to threaten the reliability of conventional copper interconnects, including the limited current carrying capacity and evident electromigration. The exceptional physical and chemical properties of the carbon nanotube (CNT) make it a promising candidate as the future interconnect material. However, the development of CNT interconnects has long been impeded by the strong CNT-substrate interaction and the poor process compatibility with semiconductor technologies.